Shona Illingworth - topologies of air - Downey, Anthony ca. 20. Jh (The Power Plant, 2022)
"Topologies of Air" and "Lesions in the Landscape" are two major bodies of work by Shona Illingworth. Informed by the artist’s long-term investigations into individual and societal amnesia, these projects critically examine the devastating psychological and environmental impacts of military, industrial, and corporate transformations of airspace and outer space. Employing interdisciplinary research and collaborative processes, Illingworth’s practice uses creative methodologies to visualize and interrogate this proliferating exploitation of airspace. Through the development of a proposed new human right, Topologies of Air and Lesions in the Landscape connect diverse cosmologies, knowledges, and lived experiences to counter the colonization of the sky and protect individuals, communities, and ecologies from ever-increasing threats from above.
Contributions by Caterina Albano, Amin Alsaden, Jill Bennett, Giuliana Bruno, Martin A. Conway, Anthony Downey, Conor Gearty, Derek Gregory, Nick Grief, Andrew Hoskins, Catherine Loveday, Issie MacPhail, William Merrin, Renata Salecl, Gabriele Schwab, Gaëtane Verna
Keywords: Illingworth, Shona -- 1966-